2020
DOI: 10.1111/sum.12583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphogypsum and water treatment residual application on key chemical and biological properties of clay soil and maize yield

Abstract: The reuse of phosphogypsum (PG) and water treatment residual (WTR) waste for agricultural purposes is a possible option to improve the soil properties and increase the crop yield. The present study was conducted during the 2014 growing season in How to cite this article: Mahmoud E, Ghoneim A, El Baroudy A, et al. Effects of phosphogypsum and water treatment residual application on key chemical and biological properties of clay soil and maize yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…phosphaticum, and P. fluorescens, and treated with 50 g PG kg −1 significantly reduced soil EC. Additionally, [28] showed that the pH and EC decreased significantly (p < 0.05) with increased PG application rates. For example, PG at a rate of 10 ton ha −1 in clay soil with maize plants showed a higher reduction in EC, ranging from 26% with the recommended nitrogen fertilizer (NF) with the water treatment residual at 5 t ha −1 (WTR5) to 48% for NF+PG10 compared with the other treatments.…”
Section: Soil Physicochemical Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations
“…phosphaticum, and P. fluorescens, and treated with 50 g PG kg −1 significantly reduced soil EC. Additionally, [28] showed that the pH and EC decreased significantly (p < 0.05) with increased PG application rates. For example, PG at a rate of 10 ton ha −1 in clay soil with maize plants showed a higher reduction in EC, ranging from 26% with the recommended nitrogen fertilizer (NF) with the water treatment residual at 5 t ha −1 (WTR5) to 48% for NF+PG10 compared with the other treatments.…”
Section: Soil Physicochemical Characteristicsmentioning
confidence: 96%
“…phosphaticum, and Pseudomonas fluorescens and treated with 30 g PG kg −1 . Mahmoud [28] demonstrated that the soil microbial biomass, CO 2 evolution, and dehydrogenase activity (DHA) increased significantly in maize plants with the application of PG (10 t ha −1 ) with nitrogen fertilizer (285 kg N ha −1 ).…”
Section: Microbial Communities and Soil Enzyme Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…WTR are mainly composed of finer mineral particles (Petterle et al, 2018) and, thus, their application in sandy soils may maintain or increase the cation exchangeable capacity and water holding capacity (Heil & Barbarick, 1989; Ibrahim et al, 2015, 2020; Mahmoud et al, 2020). Furthermore, BS can provide significant amounts of organic matter and nutrients such as phosphorus and nitrogen (Mossa et al, 2020; Pereira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%